Dissection of partial 21q monosomy in different phenotypes: clinical and molecular characterization of five cases and review of the literature. Issue 1 (December 2016) - Errichiello, Edoardo; Novara, Francesca; Cremante, Anna; Verri, Annapia; Galli, Jessica; Fazzi, Elisa; Bellotti, Daniela; Losa, Laura; Cisternino, Mariangela; Zuffardi, Orsetta
Abstract Background Partial deletion of chromosome 21q is a very rare chromosomal abnormality associated with highly variable phenotypes, such as facial dysmorphic features, heart defects, seizures, psychomotor delay, and severe to mild intellectual disability, depending on the location and size of deletions. So far, three broad deletion regions of 21q have been correlated with the clinical phenotype. Results We described the clinical and genetic features of three family members (father and two siblings) and other two unrelated patients with very wide range in age of diagnosis. All of them showed intellectual disability with very variable symptoms, from mild to severe, and carried 21q interstitial deletions with different sizes and position, as detected by conventional karyotype and array-CGH. Conclusions Our study provided additional cases of partial 21q deletions, allowing to better delineate the genotype-phenotype correlations. In contrast to previous observations, we showed that deletions of the 21q proximal region are not necessarily associated with severe phenotypes and, therefore, that mild phenotypes are not exclusively related to distal deletions. To the best of our knowledge, this is the first report showing 21q deletions in adult patients associated with mild phenotypes, mainly consisting of neurobehavioral abnormalities, such as obsessive-compulsive disorders, poor social interactions and vulnerability to psychosis.